Host tree species effects on long-term persistence of epiphytic orchid populations - Ramírez-Martínez, Adriana; Ticktin, Tamara; Mondragon, Demetria (Frontiers in Ecology and Evolution, 2022)
The destinies of epiphytic orchids are linked to their host trees. However, there is little information on if differences in host characteristics can affect the long-term persistence of orchid population, and how this might vary under different climatic conditions. We compared the population dynamics of two epiphytic orchid species, Alamania punicea and Oncidium brachyandrum growing on two host trees with contrasting leaf phenologies: the deciduous Quercus martinezii and the semideciduous Q. rugosa, over three years with varying levels of rainfall. Using data from > 500 individuals growing on 63 host trees, we applied linear mixed effects models, Integral Projection Models, and Life Table Response Experiments to identify the effects of host tree on orchid vital rates and population growth rates. For both orchid species, survival and growth did not differ between host species during wettest year. However, during the driest year both vital rates were higher on the semi-deciduous host Q. rugosa than on the deciduous Q. martinezii. Host species did not affect fecundity for A. punicea, but for O. brachyandrum fecundity was higher on the deciduous host. For A. punicea, λ values were similar between hosts during the wettest and intermediate years, but significantly lower (Δ λ=0.24) on the deciduous than on the semi-deciduous host during the driest year. This was due primarily to lower survival on the deciduous host. For O. brachyandrum, λ was slightly higher (Δ λ=0.03) on the deciduous than the semideciduous host during the wettest year, due to higher growth and reproduction. However, during the intermediate and driest years, λ values were significantly higher on the semi-deciduous than on the deciduous host (Δ λ=0.13 and 0.15 respectively). This was due to higher survival and growth. A. punicea populations appear more vulnerable to dry conditions than O. brachyandrum, likely due to its smaller psuedobulbs, and hence lower water-storing capacity. Our results show that host tree species can both influence the vital rates and the long-term dynamics of orchid populations, and these effects vary across orchids species and over time. Our results highlight the importance of maintaining a diversity of host trees to ensure long-term population persistence.